Penyuluhan Hidup Bersih dan Sehat dengan Cuci Tangan dan Sikat Gigi di SMP Swasta Pembangunan Desa Sait Buttu Saribu, Kecamatan Pamatang Sidamanik, Kabupaten Simalungun - Audia Fadilla; Mutiawati Mutiawati; Dina Mariani Siregar; Rheny Windi Nabila; Intan Aulia; Rafika Shahira Adisti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Counseling on Clean and Healthy Living Behavior (PHBS) in schools is an important step in instilling the habit of maintaining personal hygiene from an early age. This Real Work Lecture program is carried out with the aim of increasing students' understanding and awareness of the importance of PHBS, especially through the habit of washing hands with soap and brushing their teeth in the right way. The activity took place at the Sait Buttu Saribu Village Development Private Junior High School, Pamatang Sidamanik District, Simalungun Regency, using counseling, demonstration, and direct practice methods. This program involved six students, two acted as presenters and four others as companions, as well as all grade IX students as participants. In addition to providing materials and practices, this activity also encourages active participation of students through question and answer sessions and discussions on the importance of maintaining personal health and the surrounding environment. With direct involvement, students not only understand theory, but are also able to apply clean and healthy behaviors in daily life. The results of the activity showed that students were able to re-practice the material given, including the stages of washing hands and brushing their teeth correctly. It is hoped that through this activity, students can implement PHBS in a sustainable manner at school and at home, as well as become an example in encouraging a healthy living culture in the surrounding environment. This program is also expected to make a positive contribution to improving the quality of public health in general through healthy living habits from school age.